Peran Kompensasi dan Kepemimpinan dalam Meningkatkan Engagment Karyawan Gen Z - Varika, Noor; Sutrisno, Sutrisno; Kurniawan, Bayu (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze and prove the influence of compensation, discipline, and leadership on employee engagement of Gen Z at PT Pura Barutama Total Security System. The total population reached 309 employees, while the sample used in this study consisted of 174 employees. The method used by the researcher to select the research sample was purposive sampling. Hypothesis testing in this study used multiple linear regression analysis techniques. The results of the study show that compensation has a positive and significant effect on employee engagement with a t-test value of 9.537 > 1.654 t-table and a significance value of 0.000 < 0.05. The leadership variable has a positive and significant effect on employee engagement with a t-test value of 3.555 > 1.654 t-table and a significance value of 0.000 < 0.05. The value of the coefficient of determination test is 86.5%, indicating that most of the variation in Employee Engagement (Y) can be explained by Compensation (X1) and Leadership (X2).